Probing electron–hole coherence in strongly driven 2D materials using high–harmonic generation - Heide, Christian; Kobayashi, Yuki; Johnson, Amalya C.; Liu, Fang; Heinz, Tony F.; Reis, David A.; Ghimire, Shambhu (Optica, 2022)
Under strong electromagnetic excitation, electron–hole (e-h) pairs may be generated in solids, which are subsequently driven to high energy and high momentum, producing high harmonics (HH) of the driving field. The HH efficiency depends on the degree of coherence between the driven electron and hole created by the laser field. Here, we disrupt this e-h coherence in an atomically thin semiconductor by photodoping via incoherent e-h pairs. We observe a strong, systematic harmonic order-dependent intensity reduction. This trend is explained by an exponential decay of the inter-band polarization, proportional to the sub-cycle excursion time of the e-h pair. Our study provides a platform to probe the importance of many-body effects, such as excitation density-dependent decoherence time for strongly driven electrons without the need of ultrashort laser pulses.